Multi-material and multi-scale platform for robotic based in situ bioprinting - Andrea Guerra; Gabriele Maria Fortunato; Elisa Batoni; Giovanni Vozzi; Carmelo De Maria (Results in Engineering)
This work aims to develop a robotic system capable of performing multi-material, multi-scale, and multi-tool in situ bioprinting, enabling the fabrication of constructs that recapitulate the complexity of natural tissues at different scales. Starting from a previously developed robotic platform, namely IMAGObot (a 5 Degree of Freedom robotic manipulator), new printing tools were integrated with a new automatic tool-change to allow for fully automated multi-tool printing. Mechanical supports and electronic connections were created to integrate the new inkjet and valve-jet printing tools on the platform, together with the existing extrusion-based bioprinting tool. The automated tool change features specific Radio-Frequency Identification tags, introducing the robot's capability to autonomously locate and recognize the tool to connect with. Control algorithms for the new tools were implemented for printing path planning. The multi-scale in situ bioprinting procedure was validated by simulating a multi-tool and multi-material printing process in a relevant anatomical environment consisting of a human skull phantom with tissue damage at the bone tissue level. IMAGObot was able to successfully reconstruct the skull defect by autonomously alternating different bioprinting technologies and light curing of the deposited biomaterial, thus recapitulating different features of the damaged biological tissue.